The recruitment and selection process for the best marketing personnel in technical organization - Mat, Eshah (2009)
This study proposes that the best Marketing Personnel (MP) can be hired through the systematic recruitment and selection process. The review of past literature reveals that there is a variety of techniques applied to make the hiring process more efficient and suit with the vacancies. The objectives of the study are to explore the recruitment and selection techniques as well as selection criteria applied by organization in hiring MP and to suggest training needs by MP for career development. Usable 107 returned mailed questionnaires were received out of 900 mailed to organizations and the data were analyzed pertaining to the objectives of the study. The data were analyzed using descriptive statistic under frequency and also factor analysis before further analyzed using simple linear regression.The findings of the present study reveal that the organizations do practice external recruiting techniques in recruitment process whereby interview and job knowledge test were used in the selection process. Communication skill is the most important criteria in selection. Furthermore, there are needs of training to enhance capabilities of MP. In conclusion, the combination of good recruitment and selection as well as training will contribute to the best MP in the organizations.